On a fractional magnetic Schrödinger equation in R with exponential critical growth. (June 2019) - Ambrosio, Vincenzo
Abstract: We deal with a class of fractional magnetic Schrödinger equations in the whole line with exponential critical growth. Under a local condition on the potential, we use penalization methods and Ljusternik–Schnirelmann category theory to investigate the existence, multiplicity and concentration of nontrivial weak solutions.